The religious faith of the inmates of the Sarita Colonia del Callao-Peru prison - A psychoanalytic analysis - Lazarte Ugarteche, Armando Gabriel (2020)
This exploratory study analyzed under the perspective of psychoanalysis takes us to the origin of the religious devotion of Sarita Colonia to commit Crime made by subjects that are not free and serve sentence in the Penal Center of Callao. For this reason they have made profound Interviews  to ten interns at Sarita Colonia Penal , answers that were analyzed based on Freud’s psychoanalyst Theory , post freudians authors and some catholic priests that have made investigations of popular religious believings in our country. These findings are a exposed and analyzed with the purpose of generating interest in future professionals for them to widen  and deepen the knowledge of  belief in subjects that do delinquency , understanding that religion forms part of people ( individuals) in a Historic- Social specific Frame.